2020
DOI: 10.12681/mms.23482
|View full text |Cite
|
Sign up to set email alerts
|

Benthic foraminifera and brachiopods from a marine cave in Spain: environmental significance

Abstract: Sediment samples from a marine cave in the Murcia region (eastern Spain) were analysed for grain size, total benthic foraminiferaand dead brachiopoda to obtain environmental information through physical and ecological data in order to understandthe benthic communities of cave environments and their ecological significance. A total of 100 foraminiferal and 7 brachiopodspecies were classified, highlighting the first occurrence in the western Mediterranean of Gwynia capsula (Jeffreys, 1859). Statistical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The finding of living specimens of the micromorphic species G. capsula is of particular interest. This species has been reported mostly as dead specimens and disarticulated valves on cave sediments from a small number of caves in the Adriatic (Lošinj Island, Croatia: Simon, 2015; Simon & Willems, 1999); Levantine Sea (Cyprus: Jimenez et al., 2019) and the Hybero‐Provencal basin (CT12 cave, Murcia: Bergamin et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The finding of living specimens of the micromorphic species G. capsula is of particular interest. This species has been reported mostly as dead specimens and disarticulated valves on cave sediments from a small number of caves in the Adriatic (Lošinj Island, Croatia: Simon, 2015; Simon & Willems, 1999); Levantine Sea (Cyprus: Jimenez et al., 2019) and the Hybero‐Provencal basin (CT12 cave, Murcia: Bergamin et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mediterranean, being typical of the infralittoralcircalittoral zone (Logan 1979(Logan , 2003Logan et al 2004) but is also commonly found in caves (Taddei Ruggiero 1994Ruggiero , 1996Grobe & Lüter 1999;Rosso et al 2013;Gerovasileiou et al 2015;Sanfilippo et al 2015;Guido et al 2017;Jimenez et al 2019;Bergamin et al 2020). Argyrotheca cuneata is also reported from the Northeastern Atlantic (Logan 1993).…”
Section: Taxonomic Compositionmentioning
confidence: 99%
“…Megathiris detruncata (Gmelin, 1791), a representative of the family Megathyrididae, is one of the most common species in both caves. It is common throughout the Mediterranean and Northeastern Atlantic (Logan 1979(Logan , 1993(Logan , 2003Harmelin et al 2003;Gerovasileiou et al 2015;Sanfilippo et al 2015;Gerovasileiou & Bailly 2016;Bergamin et al 2020). It is characterized by the broadly transverse shell ornamented by rounded ribs (Figure 3(a-d)).…”
Section: Taxonomic Compositionmentioning
confidence: 99%
See 2 more Smart Citations